PENGARUH LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP NILAI PASAR - Yulianto, Franky Christian; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Capital market is one of the alternatives for the company to seekfor fund source and as the facility for investors toinvest their capital. The investors conduct price earnings ratio analysis to the stock because price earnings ratiocan describe the company performance in the future. When the price earnings ratio of stock is high, the profitgrowth which is expected by the investors will be high as well. This research is aimed to find out the influence ofliquidity, solvability, activity, and profitability to the market value of automotive companies which are listed inIndonesia Stock Exchange. The population is the financial statement of go public automotive companies. Thesample share 12 automotive companies which are listed in the IDX from 2010 to 2014.The result of the researchshows that liquidity, solvability and activity do not have any influence to the market value of automotivecompanies which are listed in Indonesia Stock Exchange. Meanwhile, profitability has negative influence to themarket value with its significance value is 0.042.Keywords: Liquidity, solvability, activity, profitability, market value.